Supervising Distance Students: Practice and Experience at The Open University of Tanzania - Kigadye , Emmanuel (West African Journal of Open and Flexible Learning, 2022)
Supervising doctoral candidates through a distance mode of delivery poses many challenges for both students and supervisors. The paper presents an overview at the practice and experience of supervising distance students at the Open University of Tanzania and tries to link them with best practices learned from the “DIES/CREST Online Training Course for Supervisors of Doctoral Candidates at African Universities”. Supervision practice and roles at OUT are explained and data on trends of Doctoral candidate enrolment is presented and discussed. Supervision supporting infrastructure is also outlined and discussed. The paper also highlights challenges facing supervising distance students that include; spatial and temporal, workload, technological, giving feedback and cultural challenges. Strategies for effective distance supervision are narrated and discussed and finally, the paper gives conclusions and recommendations based on the knowledge gained from the training and best practice elsewhere.
Keywords: Distance Learning; Doctoral students; Supervision Practices and Experience